Corporate governance and post-bankruptcy reorganisation performance: Evidence from Thailand - Chitnomrath, T.; Evans, Robert; Christopher, T. (Emerald Group Publishing Limited, 2011)
Purpose - This research investigates the role of key corporate governance mechanisms in determining a firm's post-bankruptcy performance following reorganisation. Design/Methodology/Approach - The study is based in agency theory and uses a unique sample of 111 filing companies whose reorganisation plans have been confirmed by the Thai Central Bankruptcy Court during the period of 1999-2002. Findings - The results indicate that monitoring and incentive mechanisms are significant determinants of a firm's post-bankruptcy performance. The key monitoring mechanism is ownership concentration, measured by shares held by the largest shareholder, whereas the critical incentive mechanisms are cash compensation and percentage of common shares held by the plan administrator. The results indicate that these mechanisms can mitigate agency problems in previously insolvent companies and increase post-bankruptcy performance over a three year period. Originality/Value - The study is timely given that many organisations are facing rebuilding programs following the impact of the global financial crisis. Prior research in Thailand and elsewhere has not measured bankruptcy reorganisation outcomes in terms of the difference of actual financial performance to predicted performance and in relation to the governance factors of the reorganisation process. Neither has this aspect been considered within an agency theory framework. This provides a unique opportunity to consider these variables based on the theoretical framework of agency theory and to evaluate the importance of governance mechanisms in reorganisation proceedings.